2023
DOI: 10.1039/d3py00048f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding differences in rate versus product determining steps to enhance sequence control in epoxide/cyclic anhydride copolymers

Abstract: One-pot synthesis of random, gradient, and block polyesters via the ring opening copolymerization of epoxides and cyclic anhydrides is investigated using simple yttrium salt catalysts. Impact of rate versus product determining steps is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These data are consistent with a bias towards the chromophore being incorporated at the start of the reaction. Addition of the AAQ monomer presumably has a lower activation energy than CHO in this case, and a bias towards early/late incorporation is expected if the activation Polymer Chemistry Paper energies are unequal, 37 since epoxide opening is reported to be the rate-limiting step. 38,39 Physical properties DSC measurements were obtained for all polymers (S3.3), from which glass transition temperatures (T g ) were obtained.…”
Section: Papermentioning
confidence: 90%
“…These data are consistent with a bias towards the chromophore being incorporated at the start of the reaction. Addition of the AAQ monomer presumably has a lower activation energy than CHO in this case, and a bias towards early/late incorporation is expected if the activation Polymer Chemistry Paper energies are unequal, 37 since epoxide opening is reported to be the rate-limiting step. 38,39 Physical properties DSC measurements were obtained for all polymers (S3.3), from which glass transition temperatures (T g ) were obtained.…”
Section: Papermentioning
confidence: 90%
“…Catalyst design has centered on the use of metal-based catalysts with designer ligands to identify the desired fast rates (often determined through single-point turnover frequencies (TOF)), dispersity control, and the ability to acquire high-molar mass polymers. These design successes are often due to tethering two cocatalysts together, allowing rates to be maintained even at low catalyst loading, as advanced by the Coates and Williams groups (Figure A). We recently identified that simple rare earth metal salts, in combination with a cocatalyst, were able to maintain fast polymerization rates and excellent polymerization control, without the need for a designer ligand (Figure B). , It is evident that these catalysts could be air-stable, with the presence of water aiding in the increase of the rate of polymerization for most monomer pairs. However, the presence of water can also be detrimental, as it leads to lower polymer molar masses than desired.…”
Section: Introductionmentioning
confidence: 99%
“…51 In another study with Meng and co-workers, a thiourea catalyst with [PPN]Cl attained a TOF of 456 h −1 at 110 °C in 10 min for CHO and PA. 54 These advances in organocatalyst design for 24,26 (B) Simple salt catalyst. 29,30 (C) Organoboron catalyst. 43 The [catalyst]/[anhydride]/[epoxide] was 1:100:500.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations